Criminal Actions of Electronic-Based Sexual Violence Post the Enforcement of Law Number 12 Of 2022 Concerning Criminal Actions of Sexual Violence - Pratiwi Ayu Sri Daulat; Sri Setiawati; Sumartini Dewi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2024)
Law Number 12 of 2022 concerning Crimes of Sexual Violence has become an important milestone in law enforcement efforts against sexual crimes, including electronic-based sexual violence. This research will discuss the legis ratio for regulating electronic-based sexual violence crimes and then discuss the harmonization of provisions for electronic-based sexual violence crimes after the enactment of Law Number 12 of 2022 concerning Sexual Violence Crimes. The research method used is normative, using a statutory approach, conceptual approach and case approach. The results of the research conclude, firstly, that the main basis for the provision of electronic-based sexual violence crimes is based on the 1945 Constitution which guarantees the protection of the rights of every citizen from all acts of violence. Second, before the legalization and enactment of Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence (UU TPKS), the legal provisions regarding sexual violence were spread across various laws and regulations. However, there are no provisions that explicitly mention electronic-based sexual violence. So that it becomes dynamic in law enforcement.